Structural studies of a water insoluble β-glucan from Pleurotus djamor and its cytotoxic effect against PA1, ovarian carcinoma cells. (15th October 2019) - Maity, Gajendra Nath; Maity, Prasenjit; Choudhuri, Indranil; Bhattacharyya, Nandan; Acharya, Krishnendu; Dalai, Sudipta; Mondal, Soumitra
Highlights: A water insoluble β-glucan (PS) was isolated from Pleurotus djamor . The structure of the β-glucan was established based on chemical and 1D/2D NMR analysis. The cytotoxic effect and wound healing assay were carried out of this β-glucan. Abstract: A water insoluble β-glucan (PS), with molecular mass ∼9.16 × 10 4 Da was isolated from the 4% alkaline extract of an edible mushroom, Pleurotus djamor and found to consist of (1→3)-β-d -glucopyranosyl moiety. The structure of the PS was elucidated on the basis of total hydrolysis, methylation analysis, periodate oxidation, and NMR experiments ( 1 H, 13 C, DQF-COSY, DEPT-135, and HSQC). The structure of the repeating unit of the polysaccharide was established as: →3)-β-d -Glcp-(1→. The water insoluble β-glucan showed cytotoxic effect against PA1 cells, where˜50% population was destroyed at 100 μg/mL concentration, and almost all cells at 250 μg/mL concentration. The wound healing assay showed significant anticarcinogenic effect against ovarian carcinoma PA1 cells after 48 h of treatment.